Saung Angklung Udjo Sebagai Ruang Edukasi Dan Pelestarian Kesenian Tradisional Sunda - Dila Fadila Hoerunnisa (UIN Sunan Gunung Djati Bandung, 2025)
Saung Angklung Udjo is a cultural center dedicated to preserving Sundanese art and heritage while serving as an important site of non-formal education, particularly for children in the Pasirlayung area of Bandung. Founded by Abah Udjo Ngalangena, this institution functions not only as a venue for traditional performances but also as a learning space where young generations are trained in angklung, dance, and other traditional musical instruments. Utilizing a hands-on, imitation-based educational approach (nimesis) without a fixed curriculum, Saung Angklung Udjo has successfully fostered an environment that nurtures creativity, discipline, and appreciation for local cultural traditions. This article applies historical methods to trace the development of Saung Angklung Udjo from its founding to its transformative role in social and educational life within the community.